Modular systems for energy usage management - Shah, Yatish T. (Boca Raton : CRC Press, 2020)
"This book examines the role of the modular approach for the back end of the energy industry- energy usage management. It outlines the use of modular approaches for the processes used to improve energy conservation and efficiency, which are the preludes to the prudent use of energy. Since energy consumption is conventionally broken down into four sectors, residential, transportation, industrial, and commercial, the discussions on energy usage management are also broken down in these four sectors in the book. The book examines the use of modular systems for five areas that cover all sectors described above: buildings, vehicles, computer and electrical/electronic products, district heating, and waste water treatment and desalination. The book also discusses the use of modular approach for energy storage and transportation. Finally, the book describes how modular approach facilitates bottom up, top down and hybrid simulation and modeling, of the energy systems from various scientific and socio/economic perspectives. Aimed at industry professionals and researchers involved in the energy industry, the book illustrates in detail how modular approach can facilitate the management of energy usage with the help of concrete industrial examples"--
OCLC-licensed vendor bibliographic record.
Keywords: Energy conservation; Energy consumption; Modularity (Engineering); TECHNOLOGY / Electricity